2021
DOI: 10.17584/rcch.2021v15i3.13049
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of cyanogenic compounds, amygdalin, prunasin, and hydrocyanic acid in almonds (Prunus dulcis Miller) for industrial uses

Abstract: The objective of this research was to quantify the concentration levels of the cyanogenic compounds, amygdalin and prunasin present in some varieties of almonds, considering their conversion to hydrocyanic acid, and their possible consumption in addition to other industrial uses, seeds of 29 commercial varieties were used of almond (Prunus dulcis Miller), evaluating its concentration and toxicity levels, taking into account the minimum degree of theoretical intake both for human consumption and for animals, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
(26 reference statements)
0
0
0
Order By: Relevance
“…At the same time, the amounts of amygdalin we determined from other fruit kernels are better than other studies in the literature. 5,10,22,24,28,29 In addition, the proposed HPLC method represents the first report on the amygdalin content of Thai fruits. As a result of the literature review, it was observed that samples of Rosaceae species were examined however researches on other families were not focused on.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At the same time, the amounts of amygdalin we determined from other fruit kernels are better than other studies in the literature. 5,10,22,24,28,29 In addition, the proposed HPLC method represents the first report on the amygdalin content of Thai fruits. As a result of the literature review, it was observed that samples of Rosaceae species were examined however researches on other families were not focused on.…”
Section: Discussionmentioning
confidence: 99%
“…Probably it was a sweet variety with any amygdalin product. Janatová reported 29 that the amygdalin amount increases during the ripening. In this study fresh fruits were used.…”
Section: Microwave Extractionmentioning
confidence: 99%
See 1 more Smart Citation